The Effect of Coronavirus Disease 2019 on Cardiovascular Diseases - Askin, Lutfu (2020)
Coronavirus disease 2019 (COVID-19) is a global pandemic affecting the world, seen in more than 1,300,000 patients. COVID-19 acts through the angiotensin-converting enzyme 2 (ACE2) receptor. Cardiovascular comorbidities are more common with COVID-19, and nearly 10% of cases develop myocarditis (22% of critical patients). Further research is needed to continue or discontinue ACE inhibitors and angiotensin receptor blockers, which are essential in hypertension and heart failure in COVID-19. Intensive research is promising for the treatment and prevention of COVID-19.